2019
DOI: 10.1080/21691401.2019.1642903
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-183 affects the development of gastric cancer by regulating autophagy via MALAT1-miR-183-SIRT1 axis and PI3K/AKT/mTOR signals

Abstract: Gastric cancer (GC) remains to be a familiar malignant tumor with poor prognosis and daunting impacts on global health. We planned to grab the latent impacts of microRNA-183 in regulating cell autophagy, thus to clarify its possible regulatory principle in GC. The miR-183 level in GC tissues and cell lines was investigated. The impacts of miR-183 dysregulation on cell biological performances including viability, apoptosis and autophagy of GC cell lines including SGC-7901 were detected. Also, cells were dispose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
(31 reference statements)
1
35
0
Order By: Relevance
“…142 Activation of the MALAT-1/miR-202/Gli2 axis is correlated with clinical features of GC, 143 and GC cell viability, apoptosis, and autophagy are partly regulated by MALAT-1/miR-183/SIRT1 and MALAT-1/miR-183/PI3K/AKT/mTOR signaling. 144 By sponging miR-1297, MALAT-1 promotes GC progression by upregulating High-mobility group box (HMGB) 2, which is involved in chemoresistance in GC. 145,146 The MALAT-1/miR-23b-3p axis confers chemoresistance by inducing prosurvival autophagy.…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…142 Activation of the MALAT-1/miR-202/Gli2 axis is correlated with clinical features of GC, 143 and GC cell viability, apoptosis, and autophagy are partly regulated by MALAT-1/miR-183/SIRT1 and MALAT-1/miR-183/PI3K/AKT/mTOR signaling. 144 By sponging miR-1297, MALAT-1 promotes GC progression by upregulating High-mobility group box (HMGB) 2, which is involved in chemoresistance in GC. 145,146 The MALAT-1/miR-23b-3p axis confers chemoresistance by inducing prosurvival autophagy.…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…12,13 Nevertheless, the regulation of ARHGAP4 in pancreatic cancer is still undiscovered microRNAs (miRNA) are small endogenous non-coding RNA molecules with a length of about 18-25 nucleotides that repress protein translation through binding to the 3ʹ-untranlated region (UTR) of their target mRNA and are significantly involved in various cancers, including pancreatic cancer. [14][15][16] High expression of miR-196a, miR-27a, miR-221, miR-143, miR-135b, miR-199b-5p and miR-21, but low expression of miR-744, miR-455-3p and miR-655, in pancreatic cancer samples were found compared with normal samples and associated with poor prognosis. 17 In addition, the expression profile of miRNAs varies even in the different locations, 18 which further confirms that miRNAs have high application value in the diagnosis, prognosis evaluation and treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 96%
“…The regulated network of hsa_circ_0091570-hsa-miR-508-5p-CHEK1/TSGA10/GSTCD was constructed and the RNAs (circRNAs and miRNAs) and genes in the network may all be novel targets for IDD. In parallel, Li et al reported that miR-183-3p regulates autophagy in gastric cancer cells by the PI3K/AKT/mTOR pathway [37]. According to previous research, the PI3K/AKT/mTOR pathway has a signi cant effect on cell growth, survival, metabolism, proliferation, and angiogenesis [38].…”
Section: Discussionmentioning
confidence: 97%